Representações sociais da dengue: aproximações e afastamentos entre o discurso da comunidade e da mídia impressa. - Milani, Miriam Ross (2012)
This study aims at apprehending the social representations (SR) elaborated by the participants of an urban area of risk and the printed media reports concerning dengue fever. It was used the Theory of Social Representation as theoretical approach. This thesis was constructed into two parts - (i) theoretical and (ii) empirical studies. The first study counted on empirical field research, included 563 participants, 263 were high school teenagers, mostly male (56%) aged between 14 and 18 years (M = 15.9, SD = 1.1) and 300 adults, mostly women (63%) aged between 20 and 59 years (M = 34.9, SD= 10.7), both groups are residents of an urban area of risk in Cuiabá, state of MT. As instruments for collecting data, it was used, biosociodemographic questionnaire, technique of free association of words (inducing stimuli: dengue fever, dengue symptoms, causes dengue and care for preventing dengue) and in depth interviews. The data generated by the questionnaires were processed by the PASW 18 and analyzed by descriptive statistics. The software Trideux was used due to its correspondence factor analysis for processing the free associations of words and variables of the participants. The discourse of the participants was processed and analyzed by the software Alceste according to its lexical analysis (standard and cross-table). The results revealed that 40% of adolescents and 43% of adult residents of the community contracted dengue fever. The semantic fields associated to dengue by the two groups were characterized by the terms disease and death, probably associated with standing water. Dengue has been represented as a synonym of the mosquito that causes the disease, which the participants associated with danger and fear, causing some symptoms (fever and headache). The symptoms of dengue were anchored in the physical-organic dimensions (bleeding, rash, muscle pain, vomiting, body ache, lack of appetite, tiredness, headache, eye pain, nauseas) and psycho affective element as sadness. The causes of dengue were associated with people, certainly when they accumulate water scarcity (water shortage), leaving standing water in uncovered containers and leave old tires, garbage, bottles and dirty yard, potential breeding sites of dengue vectors. Regarding the actions taken to prevent dengue, some procedures have been done for preventing and disease control (sand in the vases, cover the containers, to be careful, do not leave standing water, cleaning, clean the gutters), these elements were anchored in normative and behavioral dimensions diffused by media. The interview analysis showed five thematic categories named (characterization of the locality, public policy and media events, medical care and dengue hemorrhagic fever, deep rooted habits and attitudes, concepts and sources of information), complementing the knowledge of the SR shared by the studied groups. Concerning the texts originated by the newspapers Folha de Sao Paulo and A Gazeta submitted to Alceste (standard procedure and cross table analysis) five thematic categories were named (dengue epidemic in Ribeirão Preto, dengue fever, signs and special physical exams, dengue cases in Mato Grosso; potential breeding sites for dengue vector and dengue prevention practices; and scientific research on dengue). The findings of both studies showed consensual SR characterized by the educational messages diffused by the print media and are also incorporated, disseminated and propagated by the participants. On the other hand, there were some nonconsensual SR between the print media and social actors. For the first, the knowledge was guided by the sanitary and epidemiological discourse, less evident in the voice of the participants of the urban area of risk for dengue. These social actors anchored their knowledge in macro structural aspects, highlighting their historical and factual experiences, beyond the psycho emotional and relational aspects concerning the magnitude of the disease. Lastly, this study intended to contribute to the programs of healtheducation for dengue prevention and control, giving special attention to the popular knowledge.